The challenge of same-sex marriage : federalist principles and constitutional protections - Strasser, Mark Philip, 1955- (Praeger, 1999)
This text examines the constitutional dimensions of the same-sex marriage referenda in Hawaii and Alaska, and discusses the limited conditions under which the US constitution allows states to refuse recognition of same-sex marriages validly celebrated in a sister state.